ä½¿ç”¨ä»»åŠ¡åž‹æ•™å¦æ³•æé«˜èµ¤é“ä½³è‚²åˆä¸ä¸‰å¹´çº§çš„å¦ç”Ÿä½¿ç”¨åè¯ è°“è¯å¥è¯åº - Islamy, Fanrita Nabila; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
æ‘˜è¦ï¼šæœ¬æ–‡çš„ç ”ç©¶ç›®çš„æ˜¯äº†è§£åˆ©ç”¨ä»»åŠ¡åž‹æ•™å¦æ³•æé«˜èµ¤é“ä½³è‚²ä¸‰å¹´çº§å¦ç”Ÿä½¿ç”¨åè¯è°“è¯å¥çš„æ£ç¡®çŽ‡ã€‚æœ¬æ–‡çš„ç ”ç©¶å¯¹è±¡æ˜¯èµ¤é“æ•™è‚²åˆä¸ä¸‰å¹´çº§çš„å¦ç”Ÿã€‚å¦ç”Ÿä¸€å…±æœ‰44åã€‚æœ¬æ–‡ä½¿ç”¨çš„ç ”ç©¶æ–¹æ³•æ˜¯å®žéªŒæ³•ã€‚æœ¬æ–‡çš„ç ”ç©¶æ—¶é—´ä»Ž2015å¹´11æœˆ21æ—¥è‡³2015å¹´12æœˆ5æ—¥ã€‚æ ¹æ®è°ƒæŸ¥ç»“æžœï¼Œåˆ©ç”¨ä»»åŠ¡åž‹æ•™å¦èƒ½æœ‰æ•ˆåœ°æé«˜å¦ç”Ÿçš„ç§¯æžæ€§ã€å°ç»„ä»»åŠ¡æ¨¡å¼åŸ¹å…»äº†å¦ç”Ÿçš„æ—¶é—´è§‚å¿µã€åˆä½œå’Œæ²Ÿé€šèƒ½åŠ›ï¼Œè¿˜åŸ¹å¦ç”Ÿç‹¬ç«‹å¦ä¹ çš„èƒ½åŠ›ã€‚å¦ç”Ÿçš„å‰æµ‹å¹³å‡åˆ†ä¸º52åˆ†ï¼Œé€šè¿‡åˆ©ç”¨ä»»åŠ¡åž‹æ•™å¦åŽï¼ŒåŽæµ‹å¹³å‡åˆ†ä¸º88åˆ†ã€‚è¯æ˜Žäº†ä»»åŠ¡åž‹æ•™å¦æ³•èƒ½æœ‰æ•ˆåœ°æé«˜å¦ç”Ÿå¯¹åè¯è°“è¯å¥è¯åºçš„æ£ç¡®çŽ‡ã€‚ å…³é”®è¯: ä»»åŠ¡åž‹æ•™å¦æ³•ï¼Œåè¯è°“è¯å¥ï¼Œæ±‰è¯è¯åº Abstract: The aim of this research was to investigate the improvement of 3rd grade studentsâ€™ ability in constructing the right orders of nominal predicate sentence by implementing Task Based Learning Method. are students of the third grade of Bumi Khatulistiwa Junior High School with total students were 44 students. Â The research methodology was used is experimental. The research started from 21st November 2015 until 5th December 2015.The research shows that by implementing task based learning can improve studentsâ€™ activeness, time management, learning autonomy, cooperation, and communication in the studentsâ€™ group. Based on analysis of the pretest and posttest, the students only got score 52 as the means in the pretest. After implementing task based language learning method, the mean score became 88 in the post test. It is proved that task based learning method can improve the level of studentsâ€™ accuracy in ordering nominal predicate sentence. Keywords: Nominal-Predicate Sentence , Task-Based Learning , Word Order